SUSPENDED SOLID LOAD OF KAWAL AND GALANG BATANG RIVERS, AND ITS DISTRIBUTION AT GUNUNG KIJANG COASTAL AREA, EAST DISTRICT OF BINTAN - Ricky Rositasari; Indarto Happy Supriadi; Marindah Yulia Iswari (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
The research aimed to discover the runoff suspended solid load of Gunung Kijang estuary to coastal area, East District of Bintan. The research was held in May and September 2015. The total suspended solid (TSS) load in five estuaries was measured on May. On September, measurement was focused in two biggest estuaries, Kawal and Galang Batang. The TSS in coastal water area was measured both on May and September. Regarding to five estuaries measured, the lowest TSS came from Angus River while the highest comes from Kawal River. TSS load in May on both estuary were lower than in September. Suspended solid load at the lowest tide period was higher than at the highest tide at both estuaries. In May TSS load in the Kawal estuary was 528.723 mg/sc and Galang Batang estuary was 172.903 mg/sc. In September TSS load in the Kawal estuary was 720.920 mg/sc while Galang Batang estuary was 446.893 mg/sc. These results indicate that tidal patterns and current were major influence on the TSS load in estuaries. Keywords : Bintan, coastal water, estuary, load, TSS